Unveiling the Ayurvedic Approach to Water Balance and Hypertension: Insights and Connections. - Upadhyay, Abhishek; Vaidya, Meghna; Joshi, Ram Kishor (International Research Journal of Ayurveda & Yoga, 2023)
Jambu(Syzygium cumini Linn), Amra(Mangifera indica Linn), Plaksha(Ficus lacor Buch-Ham), Vata(Ficus bengalensis Linn), Kapeetana(Albizzia lebbeck), Udumbara(Ficus glomerata Roxb), Ashwattha(Ficus religiosa Linn), Bhallataka(Semicarpus anacardium Linn), Ashmantaka (Ficus rumphii Blume), Somavalka(Myrica esculenta Buch-Ham). The Mutravirajaniya Dravyas which give normal colour to the urine are; Padma(Nelumbo nucifera), Utpala(Nymphaea stellate Willd), Nalina(Variety of Kamala), Kumuda (Nymphaea nouchaki Burm.f), Saugandhika(Variety of Utpala), Pundarika(Nelumbo nucifera A white variety of Lotus), Shatapatra(Variety of Lotus), Yasthimadhu(Glycyrhhiza glabra Linn), Priyangu (Callicarpa macrophylla Vahl), Dhatakipushpa(Woodfordia fruticosa Kurtz). The Mutraverechaniya are the drugs which remove excess urine from the body called as Mutra Virechaniya Dravyas. The drugs belonging to this group are also acts as diuretic.This paper gives an attempt to summarize the drugs works in mutraveh strotas.